2011
DOI: 10.1097/igc.0b013e3182236582
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and Risk Factors for Recurrence in Malignant Ovarian Germ Cell Tumors

Abstract: This study confirms that MOGCTs have excellent prognosis, with 5-year overall survival rates of 95.6% and 73.2% in stage I and advanced stages, respectively. Age older than 45 years and treatment not in a referral center are independent risk factors for recurrence, whereas stage greater than I and yolk sac histology are independent poor prognostic indicators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 25 publications
4
59
0
3
Order By: Relevance
“…Known immunohistochemistry markers tend to lack sensitivity. Correct identification of YST is however essential, since this component is an independent poor prognostic indicator [8,9]. In a series of 49 YSTs from 45 patients, we show that HNF1, a factor necessary for early visceral endoderm differentiation, represents a highly sensitive immunohistochemical diagnostic marker for YST.…”
Section: Discussionmentioning
confidence: 99%
“…Known immunohistochemistry markers tend to lack sensitivity. Correct identification of YST is however essential, since this component is an independent poor prognostic indicator [8,9]. In a series of 49 YSTs from 45 patients, we show that HNF1, a factor necessary for early visceral endoderm differentiation, represents a highly sensitive immunohistochemical diagnostic marker for YST.…”
Section: Discussionmentioning
confidence: 99%
“…155,156 Germ cell tumors are the predominant ovarian tumor in this age group. 157 The recommended workup may include pulmonary function studies if bleomycin is being considered (see OV-B, 4 of 7; page 1146).…”
Section: Malignant Germ Cell Tumorsmentioning
confidence: 99%
“…17 Several authors demonstrated that residual disease after initial surgery is a prognostic factor for malignant germ cell tumour patients. 18 In present study 3 patients (14%) who presented with relapse had residual disease after surgery and were stage III at initial presentation.…”
Section: Discussionmentioning
confidence: 97%